Analysis of Students' Science Process Skills in Practicum-Based Animal Physiology Learning - Muhamad Tommy; Afreni Hamidah; Wilda Syahri (Postgraduate, University of Mataram, 2024)
Research on student science process skills in practicum-based animal physiology learning with the aim of analysing the science process skills possessed by Biology Education students of FKIP Jambi University. The research method used is quantitative descriptive with data collection techniques in the form of observation sheets, interviews and documentation on the implementation of practicum activities carried out by 116 Biology Education Study Programme students. The results illustrate that in the implementation of animal physiology practicum activities, the science process skills of Biology Education students class of 2022 still have a less skilled category including classification skills at 51%, prediction at 52%, interpretation at 52% and applying concepts at 54% this is due to the lack of understanding of the concept of student theory taught by lecturers so that in practicum activities less mascimal in applying new theories, while the skills of planning experiments, using tools and materials, asking questions, observation, hypothesising, and communication are skilled categories. In conclusion, based on these results, the average student's science process skills are still categorised as less skilled, there are four skills with a percentage below 63% and an average skilled category of six skills with a percentage above 69%.